The Influence of Accounting English Vocabulary Mastery and Accounting Concept Comprehension on Students’ Ability in Preparing Financial Statements in English (International Journal of Education and Literature, 2025)
Challenges faced by accounting students in producing accurate financial statements aligned with international standards, notably due to limited English proficiency. Therefore, this study examines the influence of accounting English vocabulary mastery and accounting concept comprehension on students ability in preparing financial statements in English. This study employed a quantitative method with a survey approach and multiple linear regession analysis. The research subjects are 81 accounting department students at Politeknik Negeri Banjarmasin taken with purposive sampling. Data was collected using a questionnaire and a performance task to measure vocabulary mastery, conceptual understanding, and the ability to prepare financial statements. The findings show that accounting English vocabulary mastery has a significant positive effect on students’ ability to prepare financial statements in English, while comprehension of accounting concepts does not show a significant individual effect. The adjusted R-squared value of 0.627 indicates that both variables together explain 62.7% of the variance in students’ ability. These findings emphasize that technical vocabulary mastery is a dominant factor enabling students to apply conceptual knowledge effectively in English-based financial reporting. It also highlights the importance of English for Specific Purposes (ESP) strategies in accounting education and suggests integrating vocabulary-focused learning methods to enhance students’ readiness for global accounting practices.